Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region - Quézel, Pierre (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements
Keywords: annual grasslands; broadleaved forests; circum-Mediterranean; Holocene; matorrals and steppes; Mediterranean flora; mediterranean grasslands; Mediterranean vegetation; post-glacial distribution; pre-steppe-forests (citation)

Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region - Quézel, Pierre (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements
The following values have no corresponding Zotero field: periodical: Recent Dynamics of the Mediterranean Vegetation and Landscape electronic-resource-num: 10.1002/0470093714.ch1
Keywords: annual grasslands; broadleaved forests; circum-Mediterranean; Holocene; matorrals and steppes; Mediterranean flora; mediterranean grasslands; Mediterranean vegetation; post-glacial distribution; pre-steppe-forests (citation)